ANALISIS PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Erna Murtiningsih; Retno Susanti; Dorothea Ririn Indriastuti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
Purpose of this study to know: 1) significance the effect of service quality and price on customer satisfaction, 2) significance the effect of service quality, price and customer satisfaction on customer loyalty, 3) the effect of service quality and price on customer loyalty with customer satisfaction as a variable mediation. The population of the study is the consumers of Warmindo Berseri Solo with a sample of 100 people and accidental sampling technique. Data collection techniques used observation, questionnaires and literature study. Data analysis techniques used path analysis. The results showed that service quality has a significant effect on customer satisfaction. Price has a significant effect on customer satisfaction. Service quality has a significant effect on customer loyalty. Price has a significant effect on customer loyalty. Customer satisfaction has a significant effect on customer loyalty. Customer satisfaction mediates the effect of service quality on customer loyalty. Customer satisfaction mediates the effect of prices on customer loyalty.